Impact of the spinal cord position uncertainty on the dose received during head and neck helical tomotherapy. Issue 4 (1st April 2013) - Piotrowski, Tomasz; Kaźmierska, Joanna; Sokołowski, Adam; Skórska, Małgorzata; Jodda, Agata; Ryczkowski, Adam; Cholewiński, Witold; Bąk, Bartosz
Abstract: Introduction: The study aims to establish the optimal planning risk volume (PRV) to the spinal cord (SC) for oropharyngeal cancer patients during adaptive radiation therapy with concurrent chemotherapy. Methods: Geometrical uncertainties of the SC were evaluated. Differences between planned and delivered maximum doses to each part of the SC were established for every fraction dose and for cumulative dose. Maximum doses were evaluated as a dose received in 0.5 and 1 cm 3 of the analysed part of the SC defined as C1–C2, C3–C4, C5–C6 and C7–Th1 where C n was a n ‐th cervical vertebra ( n = 1, …, 7) and Th1 was the first thoracic vertebra. Finally, relations between dose differences and geometrical uncertainties were analysed using a relative risk (RR) and the importance of the PRV dose gradient to establish an optimal PRV for the SC. Results: Prospective study based on the 875 observations from 25 oropharyngeal cancer patients was performed. The C1‐C2 part of the SC is most exposed to risk of overdosage during chemoradiation for patients with oropharyngeal cancer due to its proximity to the clinical target volume (CTV). Doses received by other parts of the SC are smaller, with the lowest dose delivered to C7–Th1. For the C1–C2, delivered dose was higher than planned dose by 11%, while for the C7–Th1, this difference was smaller than 7%. The lowest movement of individual parts of the SC were detected for the C1–C2 and the highest for the C7–Th1. The standard deviations of the mean shift ranged respectively from 0.9 to 1.4 mm and from 1.3 to 2.9 mm. For each part of the SC delivered dose was smaller than planned dose to the PRV (RR < 1). Conclusion: Our study showed that for chemoradiation of oropharyngeal cancer, using daily image guidance and proper plan adaptation scheme, the current PRV margin for the SC could be reduced to 4 mm.